A method for extracting intact intermetallic compound Mg2Si crystals from Al-Mg-Si alloys
Patent Information
- Application Number
- CN202611091847.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-23
AI Technical Summary
然而该方法用于Al-Mg-Si铝合金萃取时存在如下问题:(1)25vol%~45vol%的硝酸酒精溶液的浓度较高,实际操作中仍然会对Mg2Si晶体产生腐蚀作用,从而破坏晶体表面的纳米级生长台阶和精细结构;(2)高于45vol%的硝酸酒精溶液对Mg2Si晶体的腐蚀更严重;而低于25vol%的硝酸酒精溶液虽然可以减轻腐蚀,但是铝基体的溶解速率急剧下降,且铝表面会形成钝化膜,阻隔腐蚀反应的继续进行,导致反应在短期内基本停滞,铝基体无法在可行时间内完全溶解
[0022]本发明采用超低浓度硝酸水溶液并结合周期性补酸与超声清洗的组合工艺,实现了铝基体的缓慢、可控溶解,同时有效保护了Mg2Si晶体的表面精细结构,可获得完整、清晰的Mg2Si晶体,便于观察晶体的生长台阶、层状生长形貌等三维立体信息,为研究Mg2Si晶体的生长机理和变质元素作用机制提供了可靠的技术手段。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of technology for extracting intermetallic compounds from alloys, and specifically relates to a method for extracting complete intermetallic compound Mg2Si crystals from Al-Mg-Si alloys. Background Technology
[0002] In Al-Mg-Si alloys, the grain size and morphology of the Mg2Si phase significantly influence the mechanical properties of the alloy or composite material. Conventional two-dimensional scanning electron microscopy (SEM) observations of Mg2Si morphology typically only reveal a single cross-section of the crystal, failing to provide detailed information about its growth morphology. During crystal growth studies, the solidification time and growth stage vary at different locations; the solidification environment also differs during elemental modification, leading to variations in local composition and undercooling at different locations, resulting in varying degrees and mechanisms of modification. Therefore, theoretically, the same macroscopic sample retains crystals at different growth and modification stages; however, the crystal growth information obtainable through two-dimensional SEM is limited. Especially for face-centered cubic Mg2Si crystals, nanoscale growth information such as minute growth steps on the crystal surface, internal pores or defects, and dendrite growth protrusions is crucial for understanding the crystal growth process and the mechanisms of modification elements; however, these details cannot be observed with two-dimensional SEM.
[0003] To obtain the three-dimensional morphology of Mg2Si crystals, existing technologies have methods for extracting Mg2Si from alloys. For example, Chinese patent document CN101161833A discloses a method for extracting Mg2Si or Al8Mn5 from magnesium alloys: after removing the surface oxide scale from the magnesium alloy material, it is cut into thin slices and placed in an HNO3 ethanol solution with a concentration of 25 vol.%~45 vol.%. The extraction is carried out in an open glass reaction vessel at room temperature. After the reaction, the slices are cleaned under ultrasonic waves, then filtered and dried to obtain the final product. This invention can obtain three-dimensional Mg2Si or Al8Mn5 phases with different morphologies, facilitating intuitive observation and analysis of the morphological characteristics and growth patterns of the Mg2Si or Al8Mn5 phases. This is beneficial for in-depth and comprehensive research on the growth mechanism of the Mg2Si or Al8Mn5 phases, thereby achieving the goal of controlling the growth of the Mg2Si or Al8Mn5 phases and improving the alloy microstructure. Simultaneously, it provides a new and indirect effective method for preparing intermetallic compounds Mg2Si or Al8Mn5. However, this method has the following problems when used for Al-Mg-Si aluminum alloy extraction: (1) The concentration of 25 vol% to 45 vol% nitric acid alcohol solution is relatively high, and in actual operation, it will still corrode Mg2Si crystals, thereby destroying the nanoscale growth steps and fine structure on the crystal surface; (2) Nitric acid alcohol solution with a concentration higher than 45 vol% corrodes Mg2Si crystals more severely; while nitric acid alcohol solution with a concentration lower than 25 vol% can reduce corrosion, but the dissolution rate of the aluminum matrix drops sharply, and a passivation film will form on the aluminum surface, blocking the continued corrosion reaction, causing the reaction to basically stop in the short term, and the aluminum matrix cannot be completely dissolved within a feasible time. Therefore, simply reducing the concentration of nitric acid is not feasible.
[0004] In view of this, the present invention is hereby proposed. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the technical problem to be solved by this invention is to provide a method for extracting complete intermetallic compound Mg2Si crystals from Al-Mg-Si alloys. This method uses an ultra-low concentration HNO3 aqueous solution to extract complete intermetallic compound Mg2Si crystals from Al-Mg-Si alloys, obtaining complete three-dimensional Mg2Si crystals while minimizing the destruction of Mg2Si crystals.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for extracting complete intermetallic compound Mg2Si crystals from Al-Mg-Si alloys, comprising the following steps:
[0007] (1) Preparation of extraction solution: Prepare an aqueous solution of HNO3 with a volume concentration of 6~14 vol% as the extraction solution;
[0008] (2) Reaction extraction: After removing the surface oxide scale from the Al-Mg-Si alloy material, it is processed into thin sheets and placed in an open container containing the extraction solution for reaction extraction at room temperature;
[0009] (3) Periodic acid replenishment and ultrasonic cleaning: During the reaction extraction process, the extract is added to the open container every 1 hour; at the same time, the open container containing the extract and the sheet is placed in an ultrasonic cleaner for ultrasonic cleaning every 1 hour.
[0010] (4) Filtration: After extraction, filter the extraction mixture with filter paper and wash the container with deionized water, and then filter the washing solution again;
[0011] (5) Drying: Place the filter paper together with the filtered extract in a drying oven to dry, and the intermetallic compound Mg2Si crystals are obtained.
[0012] Optionally, the preparation method of the extract in step (1) is as follows: measure 10-20 mL of 68 vol% concentrated nitric acid, add the concentrated nitric acid to deionized water while stirring, and make up to 100 mL.
[0013] Optionally, the thickness of the sheet in step (2) is 1~3 mm.
[0014] Optionally, the sheet in step (2) may be completely immersed in the extract.
[0015] Optionally, the open container in step (2) is an open brown plastic cup or an open brown glass container.
[0016] Optionally, the thin slices described in step (2) are ground and polished before being placed into the extraction solution, and then ultrasonically cleaned with deionized water for 5 to 15 minutes.
[0017] Optionally, the amount of extract to be added in step (3) is 3 to 5 mL;
[0018] Each ultrasonic cleaning session lasts 5 to 8 minutes.
[0019] Optionally, the total reaction extraction time in step (3) is 20 to 28 hours.
[0020] Optionally, the drying temperature in step (5) is 50~70℃ and the time is 8~12 hours.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0022] This invention employs an ultra-low concentration nitric acid aqueous solution combined with a periodic acid replenishment and ultrasonic cleaning process to achieve slow and controllable dissolution of the aluminum matrix, while effectively protecting the fine surface structure of Mg2Si crystals. This results in complete and clear Mg2Si crystals, facilitating the observation of three-dimensional information such as crystal growth steps and layered growth morphology. It provides a reliable technical means for studying the growth mechanism of Mg2Si crystals and the action mechanism of metamorphic elements.
[0023] This invention targets the characteristics of the Al-Mg-Si alloy system and uses an ultra-low concentration nitric acid aqueous solution extraction system of 6~14 vol% to successfully achieve selective corrosion dissolution of the aluminum matrix and complete extraction of Mg2Si crystals. The Mg2Si crystals obtained by extraction maintain a complete two-dimensional dendritic / octahedral morphology, and the surface growth steps are clearly visible.
[0024] As is well known in the art, while high-concentration nitric acid can rapidly dissolve the aluminum matrix, it severely corrodes the surface of Mg2Si crystals; low-concentration nitric acid, although less corrosive, reacts too slowly, preventing the aluminum matrix from completely dissolving within an acceptable time. This invention successfully overcomes these technical challenges through the effective synergy of ultra-low concentration, periodic acid replenishment, and periodic ultrasonic cleaning. This invention maintains the nitric acid concentration in the extract solution above the failure threshold by periodically replenishing dilute nitric acid (3-5 mL per hour), ensuring the thermodynamic driving force of the corrosion reaction; periodic ultrasonic cleaning (5-8 minutes per hour) removes the alumina passivation film and silicon-rich residues, thoroughly corroding the aluminum matrix on the Mg2Si crystal surface, especially at Mg2Si crystal cavities, exposing fresh aluminum surfaces and ensuring the kinetic pathway of the corrosion reaction. Simultaneously, short-duration ultrasonic treatment avoids damage to the crystals; and immersion for 20-28 hours achieves better corrosion results with a reasonably controllable time.
[0025] This invention uses an aqueous solution system instead of the alcohol solution system in the prior art, which greatly reduces the risk of volatilization and combustion of organic solvents; at the same time, the corrosiveness and volatility of ultra-low concentration nitric acid are significantly lower than those of high concentration nitric acid system, which greatly reduces the harm to operators and the environment. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 Scanning electron microscope (SEM) image of Mg2Si crystals in the Al-20Mg2Si-1.0Sb alloy obtained by extraction in Example 1 of this invention;
[0028] Figure 2 Scanning electron microscope (SEM) image of Mg2Si crystals in the Al-20Mg2Si-0.5Sb alloy obtained by extraction in Example 2 of this invention;
[0029] Figure 3 Scanning electron microscope (SEM) image of Mg2Si crystals in the Al-20Mg2Si-0.5Te alloy obtained by extraction in Example 3 of this invention;
[0030] Figure 4 Scanning electron microscope (SEM) image of long rod-shaped eutectic Mg2Si in the Al-11Mg2Si alloy obtained by extraction in Example 4 of this invention;
[0031] Figure 5 Scanning electron microscope (SEM) image of Mg2Si crystals in the Al-20Mg2Si-1.0Sb alloy obtained by extraction in Comparative Example 1. Detailed Implementation
[0032] To better understand the present invention, the following embodiments further illustrate the content of the invention, but the scope of protection of the present invention is not limited to the following embodiments. Numerous specific details are set forth in the following description to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the present invention can be practiced without one or more of these details.
[0033] Unless otherwise specified, all raw materials are derived from commercially available products and do not contain any unspecified components other than unavoidable impurities.
[0034] To make the objectives and advantages of this invention clearer, the following detailed description, in conjunction with specific embodiments, illustrates a method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy and its effects. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Unless otherwise specified, the following embodiments do not include components other than unavoidable impurities. Unless otherwise specified, the raw materials and instruments used in the embodiments are conventionally selected in the art. Experimental methods not specifying specific conditions in the embodiments were implemented under conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer.
[0035] Example 1 A method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy, comprising the following steps:
[0036] (1) Preparation of extraction solution: Measure 10 mL of 68 vol% concentrated nitric acid, add the concentrated nitric acid to deionized water while stirring, and make up to 100 mL to prepare an HNO3 aqueous solution with a volume concentration of 6.8 vol% as the extraction solution.
[0037] (2) Reaction extraction: The Al-20Mg2Si-1.0Sb alloy material was ground and polished, ultrasonically cleaned with deionized water for 5 minutes, and processed into a thin sheet with a thickness of 1 mm (10 mm in length and width). The sheet was placed in an open brown plastic cup containing the extraction liquid, and the thin sheet was completely immersed in the extraction liquid. The reaction extraction was carried out at room temperature.
[0038] (3) Periodic acid replenishment and ultrasonic cleaning: During the reaction extraction process, the extract is added to the open container every 1 hour, and the amount added is 3 mL; at the same time, the open container containing the extract and the thin film is placed in an ultrasonic cleaner for ultrasonic cleaning every 1 hour, with a frequency of 40 kHz and a power of 100 W, and each ultrasonic cleaning time is 5 minutes.
[0039] (4) Filtration: After 24 hours of extraction, the extraction mixture is filtered with filter paper and the container is washed with deionized water. The washing solution is then filtered again.
[0040] (5) Drying: Place the filter paper together with the filtered extract in a drying oven and dry at 50°C for 8 hours to obtain the intermetallic compound Mg2Si crystal.
[0041] Morphological observation: The powder sample was lightly adhered to the surface of the dried filter paper with conductive tape, sputtered with gold, and then sent into a field emission scanning electron microscope for morphological observation. The results are as follows: Figure 1 As shown, the complete three-dimensional morphology of Mg2Si crystals can be clearly observed.
[0042] Example 2 A method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy, comprising the following steps:
[0043] (1) Preparation of extraction solution: Measure 20 mL of 68 vol% concentrated nitric acid, add the concentrated nitric acid to deionized water under stirring, and make up to 100 mL to prepare an HNO3 aqueous solution with a volume concentration of 13.6 vol% as the extraction solution.
[0044] (2) Reaction extraction: The Al-20Mg2Si-0.5Sb alloy material was ground and polished, ultrasonically cleaned with deionized water for 10 minutes, and processed into a thin sheet with a thickness of 2mm (length and width are 12mm respectively). The sheet was placed in an open brown plastic cup containing the extraction liquid, and the thin sheet was completely immersed in the extraction liquid. Reaction extraction was carried out at room temperature.
[0045] (3) Periodic acid replenishment and ultrasonic cleaning: During the reaction extraction process, the extract is added to the open container every 1 hour, and the amount added is 5 mL; at the same time, the open container containing the extract and the thin film is placed in an ultrasonic cleaner for ultrasonic cleaning every 1 hour, with a frequency of 40 kHz and a power of 100 W, and the ultrasonic cleaning time is 6 minutes each time.
[0046] (4) Filtration: After 24 hours of extraction, the extraction mixture is filtered with filter paper and the container is washed with deionized water. The washing solution is then filtered again.
[0047] (5) Drying: Place the filter paper together with the filtered extract in a drying oven and dry at a temperature of 65°C for 12 hours to obtain the intermetallic compound Mg2Si crystal.
[0048] Morphological observation: The powder sample was lightly adhered to the surface of the dried filter paper with conductive tape, sputtered with gold, and then sent into a field emission scanning electron microscope for morphological observation. The results are as follows: Figure 2 As shown, the complete three-dimensional morphology of Mg2Si crystals can be clearly observed.
[0049] Example 3 A method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy, comprising the following steps:
[0050] (1) Preparation of extraction solution: Measure 15 mL of 68 vol% concentrated nitric acid, add the concentrated nitric acid to deionized water under stirring, and make up to 100 mL to prepare an HNO3 aqueous solution with a volume concentration of 10.2 vol% as the extraction solution.
[0051] (2) Reaction extraction: The Al-20Mg2Si-0.5Te alloy material is ground and polished, ultrasonically cleaned with deionized water for 15 minutes, and processed into a thin sheet with a thickness of 1 mm (12 mm in length and width). The sheet is placed in an open brown plastic cup containing the extraction liquid, and the thin sheet is completely immersed in the extraction liquid. Reaction extraction is carried out at room temperature.
[0052] (3) Periodic acid replenishment and ultrasonic cleaning: During the reaction extraction process, the extract is added to the open container every 1 hour, and the amount added is 5 mL; at the same time, the open container containing the extract and the thin film is placed in an ultrasonic cleaner for ultrasonic cleaning every 1 hour, with a frequency of 40 kHz and a power of 100 W, and the ultrasonic cleaning time is 8 minutes each time.
[0053] (4) Filtration: After 24 hours of extraction, the extraction mixture is filtered with filter paper and the container is washed with deionized water. The washing solution is then filtered again.
[0054] (5) Drying: Place the filter paper together with the filtered extract in a drying oven and dry at 70°C for 10 hours to obtain the intermetallic compound Mg2Si crystal.
[0055] Morphological observation: The powder sample was lightly adhered to the surface of the dried filter paper with conductive tape, sputtered with gold, and then sent into a field emission scanning electron microscope for morphological observation. The results are as follows: Figure 3 As shown, the complete three-dimensional morphology of Mg2Si crystals can be clearly observed.
[0056] Example 4 A method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy, comprising the following steps:
[0057] (1) Preparation of extraction solution: Measure 10 mL of 68 vol% concentrated nitric acid, add the concentrated nitric acid to deionized water while stirring, and make up to 100 mL to prepare an HNO3 aqueous solution with a volume concentration of 6.8 vol% as the extraction solution.
[0058] (2) Reaction extraction: The Al-11Mg2Si alloy material is ground and polished, ultrasonically cleaned with deionized water for 10 minutes, processed into a thin sheet with a thickness of 1~3mm, placed in an open brown plastic cup containing the extraction liquid, the thin sheet is completely immersed in the extraction liquid, and reaction extraction is carried out at room temperature.
[0059] (3) Periodic acid replenishment and ultrasonic cleaning: During the reaction extraction process, the extract is added to the open container every 1 hour, and the amount added is 3 mL; at the same time, the open container containing the extract and the thin film is placed in an ultrasonic cleaner for ultrasonic cleaning every 1 hour, with a frequency of 40 kHz and a power of 100 W, and each ultrasonic cleaning time is 5 minutes.
[0060] (4) Filtration: After 24 hours of extraction, the extraction mixture is filtered with filter paper and the container is washed with deionized water. The washing solution is then filtered again.
[0061] (5) Drying: Place the filter paper together with the filtered extract in a drying oven and dry at a temperature of 60°C for 8 hours to obtain the intermetallic compound Mg2Si crystal.
[0062] Morphological observation: The powder sample was lightly adhered to the surface of the dried filter paper with conductive tape, sputtered with gold, and then sent into a field emission scanning electron microscope for morphological observation. The results are as follows: Figure 4 As shown, the complete three-dimensional morphology of the long rod-shaped eutectic Mg2Si can be clearly observed.
[0063] Comparative Example 1The same alloy materials and methods as in Example 1 were used, except that the extractant was a nitric acid aqueous solution with a volume concentration of 34 vol% (50 mL of 68 vol% concentrated nitric acid was measured, and the concentrated nitric acid was added to deionized water under stirring, and the volume was adjusted to 100 mL to prepare an HNO3 aqueous solution with a volume concentration of 34 vol% as the extractant).
[0064] Morphological observation: The powder sample was lightly adhered to the surface of the dried filter paper with conductive tape, sputtered with gold, and then sent into a field emission scanning electron microscope for morphological observation. The results are as follows: Figure 5 As shown, the surface corrosion is severe and irregular, and the complete three-dimensional morphology of Mg2Si crystals cannot be observed.
[0065] Comparative Example 2 The same alloy materials and methods as in Example 1 were used, with the only difference being that the extraction solution was a 3.4 vol% nitric acid aqueous solution (5 mL of 68 vol% concentrated nitric acid was added to deionized water under stirring, and the volume was adjusted to 100 mL to prepare a 3.4 vol% HNO3 aqueous solution as the extraction solution). Experiments showed that it was difficult to obtain crystalline powder within a 24-hour extraction time. Even after extending the extraction time to 36 hours, it was still difficult to obtain crystalline powder, making effective morphological observation impossible.
[0066] Comparative Example 3 The same alloy materials and methods as in Example 1 were used, except that periodic ultrasonic cleaning was not performed during the reaction extraction process, i.e., the ultrasonic cleaning step in step (3) was omitted.
[0067] Experiments showed that a gray-black passivation layer formed on the surface of the alloy sheet approximately 6 hours after the reaction began, significantly reducing the corrosion rate. Even with continued replenishment of dilute nitric acid, the alloy sheet was not completely dissolved after 24 hours, leaving a large amount of aluminum substrate residue. This comparative example demonstrates that ultrasonic cleaning can break through the alumina passivation film, expose the fresh aluminum surface, and ensure the continued progress of the corrosion reaction.
[0068] Comparative Example 4 The same alloy materials and methods as in Example 1 were used, except that nitric acid was not added during the reaction extraction process, i.e., the acid addition step in step (3) was cancelled.
[0069] Experiments revealed that approximately 3 hours after the reaction began, the corrosive power of the extract rapidly decreased as nitric acid was consumed and evaporated; after 12 hours, the corrosion reaction on the alloy sheet surface essentially ceased, and after 24 hours, the aluminum substrate was far from completely dissolved. This comparative example demonstrates that periodically adding an appropriate amount of nitric acid can effectively maintain the extract concentration and ensure the continued progress of the corrosion reaction.
[0070] In summary, this invention utilizes a low-concentration HNO3 aqueous solution to remove the aluminum matrix through controlled corrosion over a reasonable time, while minimizing damage to the Mg2Si crystals and preserving micro-steps reflecting the growth mechanism, dendrite tip protrusions, or atomically flat areas on the crystal surface. This invention leverages the sustained corrosion ability of HNO3 aqueous solution on aluminum to gradually peel off the matrix; it employs an ultra-low concentration (6-14 vol%) nitric acid extraction solution, periodically replenished to maintain the concentration, and combined with ultrasonic cleaning to break the surface passivation layer, selectively corroding the aluminum matrix; multiple short-duration ultrasonic treatments can thoroughly corrode the aluminum matrix on the Mg2Si crystal surface, especially at the voids in the Mg2Si crystals. Through these methods, the corrosion of the Mg2Si crystals by nitric acid is avoided, resulting in a complete three-dimensional morphology.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Any other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention, as long as they do not depart from the spirit and scope of the technical solutions of the present invention, should be covered within the scope of the claims of the present invention.
Claims
1. A method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy, characterized in that: Includes the following steps: (1) Prepare an aqueous solution of HNO3 with a volume concentration of 6~14 vol% as the extraction solution; (2) After removing the surface oxide scale from the Al-Mg-Si alloy material, it is processed into thin sheets and placed in an open container containing the extraction solution for reaction extraction at room temperature; (3) During the reaction extraction process, the extract is added to the open container every 1 hour; at the same time, the open container containing the extract and the sheet is placed in an ultrasonic cleaner for ultrasonic cleaning every 1 hour. (4) After extraction, filter the extraction mixture with filter paper and wash the container with deionized water, and then filter the washing solution again. (5) Place the filter paper and the filtered extract together in a drying oven to dry, and the intermetallic compound Mg2Si crystals are obtained.
2. The method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy as described in claim 1, characterized in that: The method for preparing the extract in step (1) is as follows: measure 10-20 mL of 68 vol% concentrated nitric acid, add the concentrated nitric acid to deionized water while stirring, and make up to 100 mL.
3. The method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy as described in claim 2, characterized in that: The thickness of the sheet mentioned in step (2) is 1~3mm.
4. The method for extracting complete intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy as described in claim 3, characterized in that: The sheet in step (2) is completely immersed in the extract.
5. The method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy as described in claim 4, characterized in that: The open container mentioned in step (2) is an open brown plastic cup or an open brown glass container.
6. The method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy as described in claim 5, characterized in that: Before being placed into the extraction solution, the thin slices described in step (2) are ground and polished, and then ultrasonically cleaned with deionized water for 5 to 15 minutes.
7. The method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy as described in claim 6, characterized in that: The amount of extract to be added in step (3) is 3-5 mL; Each ultrasonic cleaning session lasts 5 to 8 minutes.
8. The method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy as described in claim 7, characterized in that: The total reaction extraction time in step (3) is 20 to 28 hours.
9. The method for extracting intact intermetallic compound Mg2Si crystals from an Al-Mg-Si alloy as described in claim 8, characterized in that: The drying temperature in step (5) is 50~70℃ and the drying time is 8~12 hours.
Citation Information
Patent Citations
Method for extracting intermetallic compound Mg2Si or Al8Mn5 from magnesium alloy
CN101161833A